Litigation as a Strategy to Overcome Monopolistic Inefficiency in Sports. (15th June 2016) - Ross, S. F.
Abstract : Prior work has identified welfare problems with monopoly sports leagues that are not governed by a residual claimant: In addition to standard effects of allocative and distribute inefficiency, these leagues often reach sub‐optimal results because of bargaining costs and information problems that distort the results because of a governance structure reflecting parochial stakeholder interests. This paper hypothesizes that leading sports law cases can be viewed as strategic attempts to overcome information and bargaining costs to improve upon sub‐optimal league decisions and facilitate efficient ones. A case study approach is used to identify different ways in which litigation can be used in this manner. Copyright © 2016 John Wiley & Sons, Ltd.